Exploring global supply and demand of scandium oxide in 2030. (15th May 2023) - Phoung, Sinoun; Williams, Eric; Gaustad, Gabrielle; Gupta, Ajay
Abstract: Due to its light-weighting potential and utility in fuel cells, scandium incorporation is important to achieving decarbonization and energy efficiency. Forecasting scandium supply and demand is complex due to lack of public data and uncertainty in potential new market sectors such as automobiles and commercial airplanes. Consultants provide forecasts, but the underlying assumptions are unclear, and results differ by firm. We explore global supply and demand of scandium oxide in 2030 using public data and information from government, consultants, and literature to analyze two possible scenarios: business-as-usual share of scandium products in sectors and an assumed additional 10% share, including new applications. For supply, in addition to current producers, planned and proposed scandium oxide suppliers are assessed and ranked to match demand scenarios. Current production is 14–23 tonnes per annum, if proposed projects are built by 2030 the maximum total is approximately 1, 800 tonnes. The business-as-usual scenario would result in 38 tonnes of production per annum in 2030. The assumed additional 10% share scenario suggests supply would be sufficient to meet all demand at 260 tonnes in 2030, except in automobiles, which could use 5, 300 tonnes. Scandium oxide production would need to expand by 3, 700 tonnes in 2030 over proposed projects to meet the additional 10% share. Adoption is not ensured if price and supply volatility remain. The most critical drivers of future scandium oxide demand are its price and availability. Highlights: The proposed global scandium oxide supply projects result in 1, 800 tonnes in 2030. Scandium oxide demand reaches 38 tonnes the in business-as-usual scenario in 2030. Demand reaches 5, 500 tonnes in the assumed additional 10% scenario in 2030. Automobile industry demands 5, 300 tonnes in the additional 10% scenario in 2030. This leads to the question of mass adoption or mass production first.